PERDAMAIAN SEBAGAI PROSES RESOLUSI KONFLIK KELUARGA KRISTEN - Lourine S Joseph (IAKN Ambon, 2018)
Peace, tranquility, stability and happiness are the desires of human life, as well as Christian families. Consciously or not every indifidu in Christian family life craves for such a life situation. But in fact, conflict is the reason Christian families live in peace, unrest, unhappiness. Love and compassion are lost due to the sense and stance that emerges as a form of a far life of peace. Inner feelings and wounds exceed the will of peace, the stance exceeds the hope of peaceful living. Peace is one way of conflict resolution processes that occur including Christian family conflicts. The trick is through dialogue and communication with love and affection through conversation, dialogue with actions and attitudes, then the Christian family's peace is realized.